Anger Inhibition and Pain Modulation. Issue 12 (22nd April 2019) - Toledo, Tyler A; Hellman, Natalie; Lannon, Edward W; Sturycz, Cassandra A; Kuhn, Bethany L; Payne, Michael F; Palit, Shreela; Güereca, Yvette M; Shadlow, Joanna O; Rhudy, Jamie L
Abstract : Healthy persons with a tendency to suppress anger showed a reduced ability to inhibit pain during a neutral distractor. This could promote pain risk. Abstract: Background: The tendency to inhibit anger (anger-in) is associated with increased pain. This relationship may be explained by the negative affectivity hypothesis (anger-in increases negative affect that increases pain). Alternatively, it may be explained by the cognitive resource hypothesis (inhibiting anger limits attentional resources for pain modulation). Methods: A well-validated picture-viewing paradigm was used in 98 healthy, pain-free individuals who were low or high on anger-in to study the effects of anger-in on emotional modulation of pain and attentional modulation of pain. Painful electrocutaneous stimulations were delivered during and in between pictures to evoke pain and the nociceptive flexion reflex (NFR; a physiological correlate of spinal nociception). Subjective and physiological measures of valence (ratings, facial/corrugator electromyogram) and arousal (ratings, skin conductance) were used to assess reactivity to pictures and emotional inhibition in the high anger-in group. Results: The high anger-in group reported less unpleasantness, showed less facial displays of negative affect in response to unpleasant pictures, and reported greater arousal to the pleasant pictures. Despite this, both groups experienced similar emotional modulation of pain/NFR. By contrast, the high anger-in group did not show attentional modulation of pain. Conclusions: These findings support the cognitive resource hypothesis and suggest that overuse of emotional inhibition in high anger-in individuals could contribute to cognitive resource deficits that in turn contribute to pain risk. Moreover, anger-in likely influenced pain processing predominantly via supraspinal (e.g., cortico-cortical) mechanisms because only pain, but not NFR, was associated with anger-in.